THE STUDENTS’ INTEREST IN LEARNING ENGLISH AT THE XI CLASS IN SMA NEGERI 1 LAWE BULAN IN ACADEMIC YEAR 2021/2022 - Lisnawati; Alvin Hadi; Muhammad Tahir (STKIP USMAN SAFRI KUTACANE, 2022)
The objective of this research to know how was level the students’ interest in learning english at the xi class in SMA Negeri 1 lawe bulan in the academic year 2020/2021. The population of this research are 78 students where the researcher used total sampling where 78 students become sample in this research. This research used qualitative descritive. It employed Questionnaire as instruments. The questionnaire consist 30 item and divided 4 indicators. The result of this research showed from the students’ answer in the questionnaires. From the calculation from 4 indicators, first, it is feeling of pleasure 63% it was category High, second, students interest 64% it was category High, the third, Acceptance or Attention 59% it was category High Enough and the last, students participation 51% it was category High Enough. Then for measure students’ interest in learning englsih the total score achieved multiplied by 100% the shared with the maximum score. The result of the calculation showed the percentage of students interest in learning english which is 59,82% it was category High Enough.